Exploring Teachers’ Beliefs and Their Practice Towards CLT In EFL Classroom - Nadaa Putri; Salsabila; Meszalunna Zafira; Atik Yuliyani; Haryanti (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
Research in English as a Foreign Language (EFL) has consistently shown that teachers’ classroom practices are influenced by their pedagogical beliefs, although alignment between beliefs and practices is not always evident. This study explores junior high school teachers’ beliefs about Communicative Language Teaching (CLT) and examines the extent to which these beliefs are reflected in their classroom practices. Using a descriptive qualitative design, data were collected through semi-structured interviews and classroom observations. The findings reveal a clear misalignment between teachers’ stated support for CLT principles, such as student-centered learning, and their actual classroom practices, which remain largely teacher-centered with frequent use of the mother tongue. This gap is primarily attributed to students’ low English proficiency, low motivation, and limited technological resources. These constraints compel teachers to adapt their practices in ways that contradict their beliefs. The study highlights that mismatches between CLT beliefs and practices stem more from contextual limitations than from a lack of conceptual understanding. Practically, the findings suggest the need for context-sensitive CLT implementation, targeted professional development, and institutional support to help teachers enact communicative approaches more effectively in constrained EFL settings.